Magnetically Diluted Dy3+ and Yb3+ Squarates Showing Relaxation Tuning and Matrix Dependence - Rina Takano; Takayuki Ishida (Molecules)
A new compound [Y2(sq)3(H2O)4] (Y-sq; sq = squarate (C4O42–)) was prepared and structurally characterized. Since the RE-sq family (RE = Y, Dy, Yb, Lu) gave isostructural crystals, the objective of this study is to explore the effects of diamagnetic dilution on the SIM behavior through systematic investigation and comparison of diamagnetically diluted and undiluted forms. The 1%-Diluted Dy compounds, Dy@Y-sq and Dy@Lu-sq, showed AC magnetic susceptibility peaks without any DC bias field (HDC), whereas undiluted Dy-sq showed no AC out-of-phase response under the same conditions. The Orbach and Raman mechanisms are assumed in the Arrhenius plots, giving Ueff/kB = 139(5) and 135(8) K for Dy@Y-sq and Dy@Lu-sq, respectively, at HDC = 0 Oe. In contrast, Yb@Y-sq and Yb@Lu-sq behaved different; Yb@Y-sq can be regarded as a field-induced SIM because AC out-of-phase response was recorded only when HDC was present. On the other hand, Yb@Lu-sq showed a relaxation independent from temperature around 2 K at HDC = 0 Oe, possibly ascribed to a quantum-tunneling-magnetization mechanism. Applying HDC = 400 Oe afforded Ueff = 61.2(14) and 62.5(16) K for Yb@Y-sq and Yb@Lu-sq, respectively. The Y/Lu matrix dependence may be related to spin–phonon coupling. The dilution technique is a facile and versatile tool for modification of SIM characteristics.